1996
DOI: 10.1038/ng0796-347
|View full text |Cite
|
Sign up to set email alerts
|

Mad-related genes in the human

Abstract: Resistance to the growth inhibitory effects of TGF-beta is common in human cancers. However, the mechanism(s) by which tumour cells become resistant to TGF-beta are generally unknown. We have identified five novel human genes related to a Drosophila gene called Mad which is thought to transduce signals from TGF-beta family members. One of these genes was found to be somatically mutated in two of eighteen colorectal cancers, and three of the other genes were located at chromosomal positions previously suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
255
2
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(266 citation statements)
references
References 19 publications
5
255
2
4
Order By: Relevance
“…In addition, attenuation of the TGF␤1 response may also be due to a diminished level of intracellular TGF␤1 signaling molecules (R-Smad and/or Co-Smad) or an up-regulation of intracellular inhibitors (I-Smad) (26,27). While the levels of mRNA for Smads 2, 3, and 4 were not affected by IL-1␤, the levels of Smad7 mRNA and protein were increased.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, attenuation of the TGF␤1 response may also be due to a diminished level of intracellular TGF␤1 signaling molecules (R-Smad and/or Co-Smad) or an up-regulation of intracellular inhibitors (I-Smad) (26,27). While the levels of mRNA for Smads 2, 3, and 4 were not affected by IL-1␤, the levels of Smad7 mRNA and protein were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of TGFb responsiveness during colon carcinogenesis has been associated with genetic and epigenetic inactivation of the TGFb type II receptor Parsons et al, 1995), Smad mutations (Riggins et al, 1997), oncogenic activation of K-Ras (Higashidani et al, 2003), and induction of protein kinase C-beta II (Murray et al, 2002). However, the possible role of Evi1 in TGFb signaling in colon cancer is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…While seven Smad genes have been reported in the literature thus far, they can be classi®ed into three types according to their functions, i.e., receptor-activated Smads (Smad1 and Smad5 for BMP; Smad2 and Smad3 for TGF-b and activin), co-Smad (Smad4) and anti-Smads (Smad6 and Smad7) Derynck et al, 1996;Eppert et al, 1996;Gra et al, 1996;Hahn et al, 1996;Hayashi et al, 1997;Hoodless et al, 1996;Lechleider et al, 1996;Liu et al, 1996;Riggins et al, 1996;Thomsen, 1996;Topper et al, 1997;Yingling et al, 1996;Zhang et al, 1996). Smad2 and Smad3, the receptor-activated, TGFb signaling Smads, are known to be highly homologous with regard to amino acid sequence and structural characteristics, and both have been found to mediate TGF-b and activin signals by forming heteromers with Smad4 (Eppert et al, 1996;Gra et al, 1996;Riggins et al, 1996;Wrana and Pawson, 1997;Zhang et al, 1996). Despite extensive studies of the Smad gene family, however, no de®nitive di erences in the regulations or functions of these receptor-activated Smads have been identi®ed.…”
mentioning
confidence: 99%
“…While Smad4 was ®rst isolated as a pancreatic tumor suppressor gene (Hahn et al, 1996), mutations in the Smad2 and Smad4 genes have also been reported in other common cancers of adults (Eppert et al, 1996;Nagatake et al, 1996;Riggins et al, 1996;Uchida et al, 1996). Our ®ndings that Smad2 and Smad4 both at 18q21 were somatically mutated in a fraction of human lung cancers Uchida et al, 1996) suggested that members of the Smad gene family may play a role in the pathogenesis of lung cancer, since normal lung epithelial cells are known to exhibit a growth-inhibitory response to TGF-b (Masuda et al, 1997;Masui et al, 1986).…”
mentioning
confidence: 99%